PENGARUH KUALITAS PEMBELAJARAN GURU EKONOMI TERHADAP PRESTASI BELAJAR SISWA SMA NEGERI 15 PEKANBARU - Lidya Natasya; Suarman Suarman; RM. Riadi RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the effect of the quality of economics teacher learning on student achievement in terms of learning planning, implementation of learning and assessing learning outcomes on student achievement. The research method used in this research is descriptive quantitative. The population in this study were all class XI at SMA Negeri 15 Pekanbaru. The selected sample was 78 students with proportional random sampling technique. Data collection was carried out using a questionnaire technique for teacher teaching quality data and documentation techniques for student achievement. The results of the study are as follows: (1) there is a positive influence between the variable quality of teacher learning on student achievement of 0.381. That is, every increase in the quality of teacher learning by one unit will reduce learning achievement by 0.381 units. (2) there is a significant effect between the variables of student achievement. With a probability of 0.000<0.05. (3) the value of the coefficient of determination (R2) obtained is R square of 0.439 or 43.9%.Key Words : Kualitas pembelajaran, prestasi belajar